INTERNACIONALIZAÇÃO DE CURSOS STRICTO SENSU: UMA INVESTIGAÇÃO SOBRE A DISTÂNCIA PSÍQUICA E AS PRÁTICAS ADOTADAS - Gustavo da Rosa Borges (Universidade Federal de Santa Catarina, 2016)
The internationalization as strategy of insertion in foreign markets is not a phenomenon restricted to businesses. It is noticed also, that the higher education institutions (HEIs) are increasingly being inserted in the global market to the development of specific strategies for improving the quality and construction of specific competences that support their educational policies, research and extension. The internationalization of such organizations is not new, however, increasingly HEIs are adopting this strategy, especially for postgraduate studies courses. Aiming to verify whether the psychic distance interfere in the choice of partners of foreign universities was held an exploratory and qualitative research with seven courses at a university located in southern Brazil. The results show that the psychic distance does not determine the choice of countries, and yes, the network relationship of teachers. The network of relationships in the International Business literature was considered as an important factor to minimize negative effects of the psychic distance, providing specific conditions to acquire knowledge and skills. It has been shown also that the masters and doctoral courses are inserted in the international market of higher education with a relatively low degree of knowledge. However, in a gradual way, HEIs are acquiring the knowledge and skills necessary for cooperation with foreign universities postgraduate programs, using the network of professors and researchers.